«Vi rigger til så godt vi kan» - konturer av praksisarkitekturer som muliggjør og hindrer undervisning i materialet tre i kunst- og håndverksfaget i norsk barneskole - Pauliina Maapalo (Cappelen Damm Akademisk NOASP, 2017)
The study presented in this article is connected to the field of arts and crafts teaching and learning in Norwegian primary school and the use of wood as material. Woodwork has had varied focus and status in educational curriculums but it seems as if this status has gradually faded. The purpose of this article is to sketch the contours of woodwork practices throughout three counties, Nordland, Nord-Trøndelag and Sør-Trøndelag using a large survey and a micro ethnographic study in eight primary schools. The empirical material of the study is analysed using the theory of practice architectures as lenses. The aim of the analysis is to identify the building blocks that enable and constrain woodworking practices in Norwegian primary schools.